Rock with wings - Hillerman, Anne, 1949- (Hillerman, Tony, Leaphorn and Chee novel, 2015)
Navajo Tribal cops Jim Chee and Bernadette Manuelito, and their mentor, the legendary Lieutenant Joe Leaphorn, investigate two perplexing cases involving a missing woman and a drug bust gone bad.